COVID-19 PANDEMIC IMPLICATIONS FOR THE POLISH LABOR MARKET (Research Bulletins of the Faculty of Economic Sciences, 2021)
COVID-19 is an exogenous shock affecting the functioning of world economies and their labor markets. European countries have faced external shocks many times in the past, but these were usually economic in nature. In March 2020, economies were hit by a violent external shock, but due to other causes of the shock, the economies' response is different. Immediately after the declaration of a pandemic by the World Health Organization, the governments of most countries around the world issued administrative decisions aimed at upsetting economies. These decisions disrupted the functioning of the labor markets. Violent decisions increased unemployment and inactivit, and interfered with the employee-employer relationship. Governments wanting to mitigate the negative effects of the COVID-19 shock introduced savings solutions for enterprises. In Poland, the mechanism of response to the external shock of March 2020 was similar to that in other economies of the European Union. However, it seems that the Polish labor market is characterized by greater resilience, which is why the effects of the crisis caused by the pandemic are not so severely felt. The main aim of the article is to assess the situation on the Polish labor market during the COVID-19 pandemic. The main research question was formulated in the form of whether the COVID-19 pandemic changed the situation on the labor market in Poland in Q1 and Q2 2020 and if so, which of the labor market indicators reacted most strongly. The empirical study includes a comparative analysis of the basic indicators describing the functioning of the Polish labor market during the COVID-19 pandemic. To determine changes in the situation on the labor market in Poland, the results of the Labor Force Survey (LFS) on the number of economically active and inactive and their detailed characteristics were used. The source of information on the number of economically active and inactive were the databases of the Central Statistical Office and, supplementarily, Eurostat. The empirical study period generally covered Q1 and Q2 2020.
Keywords: Keywords: labor market, exogenous shock, workers, COVID-19, Poland